Survey of American College of Surgeons Committee on trauma members on firearm injury: Consensus and opportunities. Issue 5 (May 2017) - Kuhls, Deborah A.; Campbell, Brendan T.; Burke, Peter A.; Allee, Lisa; Hink, Ashley; Letton, Robert W.; Masiakos, Peter T.; Coburn, Michael; Alvi, Maria; Lerer, Trudy J.; Gaines, Barbara A.; Nance, Michael L.; et al.
Abstract : BACKGROUND: In the United States, there is a perceived divide regarding the benefits and risks of firearm ownership. The American College of Surgeons Committee on Trauma Injury Prevention and Control Committee designed a survey to evaluate Committee on Trauma (COT) member attitudes about firearm ownership, freedom, responsibility, physician-patient freedom and policy, with the objective of using survey results to inform firearm injury prevention policy development. METHODS: A 32-question survey was sent to 254 current U.S. COT members by email using Qualtrics. SPSS was used for χ 2 exact tests and nonparametric tests, with statistical significance being less than 0.05. RESULTS: Our response rate was 93%, 43% of COT members have firearm(s) in their home, 88% believe that the American College of Surgeons should give the highest or a high priority to reducing firearm-related injuries, 86% believe health care professionals should be allowed to counsel patients on firearms safety, 94% support federal funding for firearms injury prevention research. The COT participants were asked to provide their opinion on the American College of Surgeons initiating advocacy efforts and there was 90% or greater agreement on 7 of 15 and 80% or greater on 10 of 15 initiatives. CONCLUSION: The COT surgeons agree on: (1) the importance of formally addressing firearm injury prevention, (2) allowing federal funds to support research on firearms injury prevention, (3) retaining the ability of health care professionals to counsel patients on firearms-related injury prevention, and (4) the majority of policy initiatives targeted to reduce interpersonal violence and firearm injury. It is incumbent on trauma and injury prevention organizations to leverage these consensus-based results to initiate prevention, advocacy, and other efforts to decrease firearms injury and death. LEVEL OF EVIDENCE: Prognostic/epidemiologic study, level I; therapeutic care, level II.